Cell Stress Signaling Cascades Regulating Cell Fate - Gundamaraju, Rohit; Vemuri, Ravichandra; Chong, Wai C.; Geraghty, Dominic P.; Eri, Rajaraman (Current Pharmaceutical Design, 2018)
Initiating anti-apoptotic signaling or triggering cell death depends to a great extent on the nature or source of cellular stress and cell type. Interplay between each stress response eventually determines the fate of stressed cell. Numerous factors induce cell death by a number of pathways including apoptosis, autophagy and necrosis. Not surprisingly, some of the pathways are interrelated to each other through a mediator that could articulate the entire mechanism. The present review attempts to consolidate all the pathways included in intrinsic cellular stress such as oxidative stress and autophagy, endoplasmic reticular stress (ERS) and mitophagy and apoptosis as fate in cell stress. These stress responses are a hallmark of numerous diseases including neurodegenerative diseases, diabetes and cancer. Understanding the cross-talk between different intrinsic cell stress responses will help to develop new therapeutic targets and hence lead to the development of new therapeutics.
Keywords: oxidative stress